In vitro and in vivo identification of metabolites of magnoflorine by LC LTQ‐Orbitrap MS and its potential pharmacokinetic interaction in Coptidis Rhizoma decoction in rat. (22nd January 2015) - Xue, Baojuan; Zhao, Yuanyuan; Miao, Qing; Miao, Peipei; Yang, Xiaoyan; Sun, Guixia; Su, Jin; Ye, Jing; Wei, Baohong; Zhang, Yuanyuan; Zhang, Yujie
Abstract Magnoflorine, an important aporphine alkaloid in Coptidis Rhizoma, is increasingly attracting research attention because of its pharmacological activities. The in vivo and in vitro metabolism of magnoflorine was investigated by LC LTQ‐Orbitrap MS. In vivo samples including rat urine, feces, plasma and bile were collected separately after both oral (50 mg kg−1) and intravenous administration (10 mg kg−1) of magnoflorine, along with in vitro samples prepared by incubating magnoflorine with rat intestinal flora and liver microsome. As a result, 12 metabolites were found in biological samples. Phase I metabolites were identified in all biological samples, while phase II metabolites were mainly detected in urine, plasma and bile. In a pharmacokinetic study, rats were not only dosed with magnoflorine via oral (15, 30 and 60 mg kg−1) and intravenous administration (10 mg kg−1) but also dosed with Coptidis Rhizoma decoction (equivalent to 30 mg kg−1 of magnoflorine) by intragastric administration to investigate the interaction of magnoflorine with the rest of compounds in Coptidis Rhizoma. Studies showed that magnoflorine possessed lower bioavailability and faster absorption and elimination. However, pharmacokinetic parameters altered significantly (p < 0.05) when magnoflorine was administered in Coptidis Rhizoma decoction. Oral gavage of Coptidis Rhizoma decoction decreased the absorption and elimination rates of magnoflorine, which revealed that there existed pharmacokinetic interactions between magnoflorine and the rest of ingredients in Coptidis Rhizoma. Copyright © 2015 John Wiley & Sons, Ltd.